Answer: a) 3 and -3 b) 4 and 2
c) 3.5 and 2.5 d) 5.5 and 0.5 e) This is due to the difference in the coefficient of (x-3)² and the value at the right side of each equation.
Step-by-step explanation:
a) 3x²-9 = 0
3x² = 0+9
3x² = 9
Dividing both sides by 3
x² = 9/3
x² = 3
x = √3
x = +3 and -3
b) (x-3)² = 1
Taking square root of both sides to remove the square,
√(x-3)² = √1
x-3 = √1
x-3 = 1 and x-3 = -1 (note that √1 is +1 and -1)
x = 4 and x = 2
c) 4(x-3)² = 1
Dividing both sides by 4 we have;
(x-3)² = 1/4
Taking the square root of both sides to eliminate the square.
√(x-3)² = √1/4
x-3 = √1/4
x-3 = +1/2 and x-3 = -1/2
x = 1/2+3 and x = -1/2+3
x = 3.5 and 2.5
d) 2(x-3)² = 12
Dividing both sides by 2 we have;
(x-3)² = 12/2
Taking the square root of both sides to eliminate the square.
√(x-3)² = √12/2
x-3 = √6
x-3 = 2.5 and x-3 = -2.5
x = 2.5+3 and x = -2.5+3
x = 5.5 and 0.5
e) The answers to questions 1 to 4 has different solutions due to the different value of the coefficient of (x-3)² and also the value at the right hand side of the equations also differs, hence, the reason for the difference in their answers.